PENGEMBANGAN MEDIA AJAR BERBASIS ANDROID PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII SMP - Ayen Arsi Sari; Fitri Apriani (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2019)
In this digital age the need for renewal in teaching media in the classroom. This research is about developing android-based learning media on the construction of flat side space. The general objective of this research is to develop an Android-based learning media on the material to build a flat side space and see the feasibility of this Android-based teaching media. This research is a development research that is R&D with 4D model. This research was conducted at Sungai Selan 1 Junior High School in Bangka Tengah Regency which was conducted in 2019. The research subjects were Grade VIII students of SMP. Data collection was carried out using questionnaires, interviews. As for the results of this study are a) The development of this android teaching media through 4D stages, namely starting to define, design, develop, and disseminate; b) Based on the assessment by material experts obtained a percentage of 93.51% so that it is included in the very feasible category, from experts based on android media teaching media get a value of 88.04%, so that it is included in the very feasible category, based on assessment by practitioners namely junior high school mathematics teachers overall the percentage was 97.58% so that it was included in the very feasible category to be used as a learning medium, on the results of the student test it was found that all questions received a